Case Report: Ensartinib as a first-line treatment for SMARCA4-deficient and EML4-ALK non-small cell lung cancer - Pan, Yanqing; Yan, Lingxin; Wang, Shaoxi; Li, Huiling; Chen, Quanfang (Frontiers in Oncology, 2025)
SMARC4 is the catalytic subunit of the SWI/SNF chromatin remodeling complex and is one of the most common altered chromatin remodeling ATPases in cancer. Studies have indicated that SMARCA4 loss is associated with highly aggressive tumors, independently predicting shorter overall and disease-specific survival. SMARCA4-deficient non-small cell lung cancer (NSCLC) primarily affects male individuals, especially smokers, and is characterized by large, aggressive tumors. Cases of SMARCA4 deletion combined with actionable driver gene mutations (e.g., ALK) are rarely reported. In this report, we describe a male non-smoker diagnosed with SMARCA4-deficient, EML4-ALK non-small cell lung cancer who has been undergoing ensartinib targeted therapy for 3 months, resulting in a significant partial response. We also propose that, from a signaling perspective, the presence of SMARCA4 deficiency may influence the sensitivity of EML4-ALK NSCLC to targeted therapy, highlighting the need for further investigation into the underlying mechanisms and the exploration of novel therapeutic approaches.